2022
DOI: 10.1021/acs.jpcb.1c08942
|View full text |Cite
|
Sign up to set email alerts
|

CO2–CH4 Exchange Process in Structure I Clathrate Hydrates: Calculations of the Thermodynamic Functions Using a Flexible 2D Lattice-Gas Model and Monte Carlo Simulations

Abstract: A two-dimensional lattice-gas model, supplemented by Monte Carlo simulations in the grand canonical ensemble, is applied to study the CO 2 /CH 4 exchange process in sI clathrate hydrates. The coverage dependence of the Helmholtz free energy, chemical potential, entropy, and degree of deformation of the sI structure is given. Two different situations are considered according to the value of the intra-and inter-species' interactions. First, lateral interactions between the guest species and water molecules are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In three recent papers from our group [56][57][58] we introduced a new 2D lattice-gas model to study the behavior of sI clathrate hydrates for different guest species such as CH 4 and CO 2 . The model was built by mapping the three-dimensional (3D) sI structure to a 2D lattice-gas model with triangular geometry (and periodic boundary conditions).…”
Section: An Application To the Problem Of Ch 4 And Co 2 Clathrate Hyd...mentioning
confidence: 99%
See 2 more Smart Citations
“…In three recent papers from our group [56][57][58] we introduced a new 2D lattice-gas model to study the behavior of sI clathrate hydrates for different guest species such as CH 4 and CO 2 . The model was built by mapping the three-dimensional (3D) sI structure to a 2D lattice-gas model with triangular geometry (and periodic boundary conditions).…”
Section: An Application To the Problem Of Ch 4 And Co 2 Clathrate Hyd...mentioning
confidence: 99%
“…There are several motivations to study a lattice-gas of trimers adsorbed on a triangular substrate: (1) the trimer is the simplest case of a polyatomic adsorbate allowing for different adsorption states on a triangular lattice; (2) the obtained results can be compared with previous analytical and computational findings available in the literature; and (3) as discussed below, several experimental systems can be modeled using trimers of different shapes. [54][55][56][57][58] A triangular (2D parallelepiped) cluster composed by m = l 1 Â l 2 sites is used to obtain the grand canonical partition function of the system. The dependence on surface coverage of the chemical potential and the configurational entropy of the adsorbed phase are obtained for the five studied systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methane is the second most abundant greenhouse gas after carbon dioxide and is the major component of natural gas. 22 They found that, in sI hydrates, CO 2 tends to displace CH 4 regardless of temperature, and this is an entropic not enthalpic effect. Finally, Paesani and co-workers used highly accurate first-principles calculations to develop many-body potential energy functions for neat methane and methane/water systems.…”
mentioning
confidence: 98%
“…Longone at al. extended their two-dimensional lattice gas model to account for mixture adsorption, thus enabling the study of CO 2 for CH 4 exchange in clathrate hydrates . They found that, in sI hydrates, CO 2 tends to displace CH 4 regardless of temperature, and this is an entropic not enthalpic effect.…”
mentioning
confidence: 99%